Isolation of shiga toxin producing Escherichia coli O157:H7 from Bovine samples of Dhaka, Bangladesh - Proma, Rhedia Tehrin (BRAC University, 2015)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Microbiology, 2015.